2019
DOI: 10.1002/cptc.201800248
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the ON/OFF Switching Performance of a pH‐Activatable Porphyrin Derivative by the Introduction of Phosphorus(V)

Abstract: An activatable photosensitizer for singlet oxygen is of significance due to its potential application in tumor‐specific photodynamic therapy and diagnosis. In this study, a pH‐activatable system that enables the specific photosensitization of singlet oxygen at a low pH value was developed based on the complexation of a porphyrin‐aniline conjugate with phosphorus(V). As a result of complexation with phosphorus, the water solubility of the porphyrin‐aniline conjugate was improved 100‐fold. Furthermore, this comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 56 publications
0
14
0
2
Order By: Relevance
“…Electron transfer can be controlled by the surrounding environment. For example, pH is an important factor to control the photoinduced electron transfer [29,30,48,80,81]. Since it has been reported that cancer cells are slightly acidic (pH 6 ~ 7) against normal tissues (pH 7 ~ 7.4) [82][83][84][85], control of the electron transfer of the photosensitizer by pH can be applied for the development of cancer-selective PDT.…”
Section: Activity Control Based On the Electron Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…Electron transfer can be controlled by the surrounding environment. For example, pH is an important factor to control the photoinduced electron transfer [29,30,48,80,81]. Since it has been reported that cancer cells are slightly acidic (pH 6 ~ 7) against normal tissues (pH 7 ~ 7.4) [82][83][84][85], control of the electron transfer of the photosensitizer by pH can be applied for the development of cancer-selective PDT.…”
Section: Activity Control Based On the Electron Transfermentioning
confidence: 99%
“…In the cases of pH-dependent 1 O 2 photosensitizers, the redox control [30,[86][87][88], the structure change [89], and the control of intersystem crossing [90] by pH have been reported as the important concepts. Several types of pH-activatable-porphyrin photosensitizers [30,88], including a phosphorus(V) porphyrin [48,81], have been reported. In addition, a self-quenching of the photoexcited molecules can be also used to control the activity [47].…”
Section: Activity Control Based On the Electron Transfermentioning
confidence: 99%
“…Since tetrakis(p-alkoxyphenyl)porphyrin phosphorus(V) complexes can oxidize protein through electron transfer under the irradiation of relatively long-wavelength visible light (~650 nm) (3,16,17), these derivatives may improve the PDT effect. Another important characteristic of the porphyrin phosphorus(V) complex is its amphiphilic nature (3,(20)(21)(22). Its solubility in water and organic solvents can be modulated by the substituents (3,16,(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Tetrakis( N -methyl- p -pyridinio)porphyrin (TMPyP) has been studied as the model compound for PDT. 17 , 29 Because the water-solubility of previously reported porphyrins was relatively low, 18 20 , 22 the use of TMPyP-based porphyrin may be advantageous for the application. To control the photosensitizing activity of TMPyP, meso -( N′ , N′ -dimethyl-4-aminophenyl)-tris( N -methyl- p -pyridinio)porphyrin (DMATMPyP, Figure 1 ) was designed and synthesized.…”
Section: Introductionmentioning
confidence: 99%